Analisis Kegiatan dan Persepsi Mahasiswa Calon Guru Biologi Terhadap Kegiatan Kuliah Praktik Lapangan Zoologi Vertebrata - sri maryanti; siti sa'adah; M Sholehah (Universitas Wiralodra, 2019)
The purpose of this study was to determine student perceptions of vertebrate zoological field study at LIPI Cibinong. The research method used is a descriptive method with survey techniques. The survey was conducted on 52 students of Biology Education department at UIN SGD Bandung. The results showed that 80.2% of students gave positive perceptions of vertebrate zoology field study because according to the students this field study could increase the meaningful learning, expand knowledge about vertebrate zoology, and strengthen the intimacy between students. Also, students believe that the field study is an implementation of Edutainment activities.